Peningakatan Media Sosial Terhadap Perkembangan Bahasa Indonesia Universitas Muhammadiyah Maumere) - Maria Firlyana Pare; Veronika Regina Nona; Paulus Kristian Andale; Elisabet Erlin; Stevanus Nong Wilfred; Yoventa Lero Rangga (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Social media has become an important part of modern society, including in Indonesia. Its rapid development has a significant influence on various aspects of life, one of which is language. The influence of social media on the development of the Indonesian language is often seen from the emergence of new terms, the use of informal language, and the simplification of sentence structures. Language changes influenced by social media raise concerns about the decline in the ability to speak good and correct Indonesian, especially among the younger generation. This study aims to determine the influence of social media on the development of the Indonesian language among teenagers. The findings include the entry of absorption from foreign languages, especially English. Words such as